Coursera Sebagai Media Pembelajaran Digital: Kajian Literatur Terhadap Efektifitas Dan Tantangannya - Septiani Agustina Siregar; Yahfizham (JOURNAL SAINS STUDENT RESEARCH, 2025)
One of the main challenges in education today is the limited flexibility of learning time and access to quality and structured learning materials. This encourages the need for learning media that is able to answer the needs of independent and globally oriented learning. Coursera, as one of the Massive Open Online Course (MOOC) platforms, offers solutions through various courses that can be accessed digitally by anyone at any time. This article is a literature review that aims to examine the effectiveness of Coursera as a digital learning media and identify challenges in its implementation. The review is conducted by analyzing a number of scientific articles and relevant sources published between 2018 and 2024. The study results show that Coursera is effective in providing quality materials, increasing motivation for self-learning, and supporting learning flexibility. However, some challenges remain, such as limited foreign language skills, the need for digital devices, and the lack of in-person mentoring support. This article recommends the need for local content integration, training on digital platform utilization, and mentoring strategies so that Coursera can be optimally used in learning.